Social Responsibility of the Private Sector in the system of Russian Healthcare; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Pozdnyakova N. V. Nadezhda Valerievna (2017, 2017)
Title screen